Sri Lanka Poverty and Welfare : Recent Progress and Remaining Challenges - Newhouse, David Locke (World Bank, Washington, DC, 2016)
Analysis of Sri Lanka’s recent progress in reducing poverty and inequality is directly relevant to the new government’s development agenda. The newly sworn-in president ran for election on a platform that featured, among other goals, inclusive growth and support to the agricultural sector. The pursuit of these and other goals of the new administration can be informed by a fuller understanding of recent developments in household living standards across the country. Yet the World Bank’s most recent poverty assessment in Sri Lanka, covering the period from 1990 to 2002, was published a decade ago. Since then, domestic economic growth, the end of the civil conflict and fluctuations in global markets has led to substantial changes in Sri Lanka’s economic environment. To inform the new government’s development policies, this report examines five topics related to recent developments in poverty and welfare. Sections two through five of the report focus on: (i) trends in poverty, welfare, and inequality since 2002, (ii) labor market outcomes associated with the observed reduction in poverty, (iii) four potential causes of this poverty reduction, (iv) the state of poverty and inequality in 2012/13, and (v) the role of social protection in reducing poverty. Section six concludes by pointing out future implications and remaining knowledge gaps to continue to reduce poverty and improve living standards. This analysis draws mainly on data from the 2002, 2006-07, 2009-10, and 2012-13 rounds of the Household Income and Expenditure Survey, supplemented by annual rounds of the labor force survey from 2002 to 2012. Since the surveys could not be conducted in parts of the Northern and Eastern provinces before 2011 due to the civil conflict, their geographical coverage varies from year to year. To ensure comparability, all historical trends presented in this report correspond to the same geographic area. With the exception of figures that are based solely on 2012-13 data, the figures exclude Northern and Eastern provinces, which account for about 12.9 percent of the total population. A more detailed description of the data is provided in appendix one.